DAMPAK MEDIA SOSIAL TERHADAP GAYA HIDUP DAN PERILAKU SOSIAL REMAJA DALAM PERSPEKTIF EKONOMI SYARIAH - Linawati, Linawati (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
This study describes the impact of social media on teenagers where the era of globalization cannot be eliminated and must be navigated, this type of research is library research. data collection by studying, reviewing, and understanding data sources available in several books, website articles and other information related to this study, the results of this study, teenagers are greatly affected by the use of social media, the influence of the family environment, lifestyle, so that it makes changes in style, life, behavior and waste of wealth. This study contributes to providing solutions and directions to teenagers to remain in the context of faith, fairness based on the principles of Islamic economics. Keywords: Social Media, Lifestyle, Social Behavior, Islamic Economics